Revisiting reasons and Kaplan 1975: towards an open wall approach to rehabilitative prisons - Schaefe, Roger (Journal of Theoretical and Philosophical Criminology, 2020)
This paper reexamines the evolution of the latent and manifest functions of American prisons originally outlined by Charles Reasons and Russell Kaplan in 1975. Reasons and Kaplan posed an important and timely question about prisons in America – tear down the wall? Reasons and Kaplan’s question emerged at a time when Americans were challenging the purpose and intended outcomes of imprisonment. Today, we find ourselves in a similar situation as we address the issue of mass incarceration – which began in the years immediately following Reason and Kaplan’s provocative and critical assessment of prison functions. Since Reasons and Kaplan posed their quasi-rhetorical question, the American prison system has transformed into an epidemic of excessive over reliance on incarceration. Consequently, penologists, policy makers, and practitioners are once again seeking answers regarding the immediate and long-term future of American prisons. In pursuit of these answers, it is imperative that we revisit Reasons and Kaplan’s article, examining our current correctional discourse.